Packaging waste generation by households: A mixed method study - Fally Fiona, Basila; Puteri Fadzline, Muhamad Tamyez; Abdul Rahman, Zahari; Yao, Liu; Ahmad Afif, Ahmarofi (Taylor & Francis, 2022)
The paper reports a study to determine the challenges faced by households in managing packaging waste, to compute the theoretical recovery rate, actual recovery rate and the total recovery potential of packaging waste generated, and to forecast the amount of waste generated by the households in Kota Samarahan, Sarawak for the next ten years. This study applies semi-structured interview, mathematical formulation and simulation modelling. The results reveal that the theoretical recovery rate among the majority of respondents is higher and the actual recovery rate among respondents is lower than it should be. There is an upward trend in the production of waste in the future.